Paradigma Filsafat Islam: Revitalisasi Pendidikan Multikultural Telaah Pemikiran TGKH. Muhammad Zainuddin Abdul Madjid Lombok - Nasri, Ulyan (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research explores the thoughts of TGKH. Muhammad Zainuddin Abdul Madjid in the context of the Islamic philosophical paradigm related to multicultural education. Utilizing content analysis method, this study examines the philosophical concepts proposed by Zainuddin in response to the challenges of multiculturalism within the context of Islamic education. The results highlight Zainuddin's inclusive, dialogic, and tolerant approach to Islamic education. He emphasizes the necessity of considering cultural and religious diversity in education, as well as a deep understanding of Islamic teachings to prevent extremism and conflict. Through the analysis of his written works, this research provides insights into Zainuddin's revolutionary vision of inclusive and multicultural Islamic education. The conclusion underscores the relevance of Zainuddin's thoughts in addressing the challenges of multiculturalism in Islamic education and its implications for building a harmonious society. By promoting an inclusive, dialogic, and tolerant Islamic education, this research offers a significant contribution to the development of the Islamic philosophical paradigm in the context of multicultural education.